Dynamics of traveling wave solutions arising in fiber optic communication of some nonlinear models - Yokus, Asif; Baskonus, Haci Mehmet (Springer, 2022)
This article deals with the applications of (1/G ')-expansion method which has recently been presented to the literature. Applying this tool on the generalized (2 + 1)-dimensional Hirota-Maccari system, perturbed nonlinear Schrodinger's equation and dispersive cubic-quintic nonlinear Schrodinger equation, new complex traveling wave solutions are founded. The solution of partial differential equations representing the phenomenon of fiber optic communication and the interrelationship of the internal dynamics of traveling wave solutions, which play an important role in the transport of energy, have been discussed. Furthermore, for a better physical understanding of the results, various graphs with the appropriate values of the parameters have been presented and the simulation has been used to support the discussion.
Keywords: Generalized (2+1)-dimensional Hirota-Maccari system; Perturbed nonlinear Schrodinger's equation; Dispersive cubic-quintic nonlinear Schrodinger equation; (1/G ')-expansion method; Complex surfaces